Social work and a Community-based Rehabilitation Program for People with Disabilities in Vietnam - Nguyen, Trang Le (Curtin University, 2017)
The research examined community based rehabilitation (CBR) as a means to enhance social and economic support for people with disability in a commune in Viet Nam. Mixed methods were used to collect information from people with disability, their families, CBR workers and policy makers. The research suggests that basic social work knowledge and skills could be integrated into training for the CBR core team to enable socio-economic support and mobilise resources in the community.